Characterization and evaluation of antioxidant potential of onion peel extract of eight differentially pigmented short-day onion (Allium cepa L.) varieties - Kalyani Gorrepati; Ashok Kumar; T. P. Ahammed Shabeer; Zareen Khan; Prashant Satpute; Sivalingam Anandhan; Thangasamy Arunachalam; Vishwanath Rohidas Yalamalle; Vijay Mahajan; Major Singh (Frontiers in Sustainable Food Systems)
Outer papery peel of onion bulb is an inevitable bio-waste generated in the course of postharvest handling and processing. Onion peels are rich source of nutraceutically important polyphenolic compounds having many therapeutic potentials. In this study, we characterized onion peel extract (OPE) of eight differentially pigmented short-day onion varieties through ultra-high-performance liquid chromatography coupled with high-resolution single stage Orbitrap spectrometry and evaluated the antioxidant potential. A total of 49 phenolic compounds were identified in this study which include 33 anthocyanin, 8 flavanol, 4 flavones, and 1 each of pyranoanthocyanin, chalcone, phenolic acid, and ellagitannins. Anthocyanin was the most abundant polyphenolic compound followed by flavanol in all the varieties. Among anthocyanin, 10 cyanidin, 10 delphinidin, 4 peonidin, 4 petunidin, 3 pelargonidin, and 2 malvidin were identified. Cyanidin-3-(6-malonylglucoside), delphinidin, and delphinidin-3-galactoside were the predominant pigment in dark red varieties (BDR and BRJ), and its abundance suggests a key role in the differential pigmentation pattern of onion peel. Total phenol content (TPC) in peels ranged from 1738.21 to 1757.76 mg GAE/100 g DW in dark red onion, 1306.58 to 1646.73 mg GAE/100 g DW in red onion, and 78.77 to 85.5 mg GAE/100 g DW in white onion varieties. The mean total anthocyanin content was maximum (28.23 mg/100 g DW) in dark red varieties (BDR) and minimum (0.11 mg/100 g DW) in white variety (BSW). Total antioxidant activity ranged from 4.71 to 79.80 μmol/g DW, 22.71 to 286.7 μmol/g DW, and 8.72 to 156.89 μmol/g DW estimated through FRAP, ABTS, and DPPH methods, respectively. In all three methods, it was maximum in dark red var. BDR and minimum in white var. BSU.